The Technolife project: an experimental approach to new ethical frameworks for emerging science and technology. (1st January 2013) - Rommetveit, Kjetil; Gunnarsdóttir, Kristrun; Jepsen, Kim Sune; Bertilsson, Thora Margareta; Verrax, Fanny; Strand, Roger
Science and technology evolve fast both as a result of their internal dynamics and the increased emphasis on research and innovation in the so-called knowledge economy. Due attention to ethical issues and aspects of emerging science and technology is called for. This paper presents the development of an experimental methodology for empirical and participatory ethics of science and technology designed to detect, understand and mediate public concerns. The experimental approach of Technolife seeks for points of mediation by which varied public concerns can become embedded institutionally and secure sets of legitimate procedures. It is an open (experimental) question if the wide variety of technologies now in sway can be handled within a uniform ethical framework or if such ethical frameworks also need to evolve more sensitised to diverse technological challenges. Thus, our methodological approach is experimental in yet a further manner in that we seek to mediate between lay ethics, whether actually existent or else merely potential, and the discourse of professional ethicists, recognising the fragmented character of both layers. The methodology forms a central part of the European Union FP7-supported, ongoing (2010) project Technolife, which gives social and sociotechnical imaginaries a key role in the ethical framework.